1998
DOI: 10.1093/nar/26.6.1522
|View full text |Cite
|
Sign up to set email alerts
|

RNase L dimerization in a mammalian two-hybrid system in response to 2',5'-oligoadenylates

Abstract: RNase L, a key enzyme in the anti-viral activity of interferons, requires activation by 2',5'-linked oligoadenylates (2-5A) to cleave viral and cellular single-stranded RNA. Here we demonstrate that 2-5A causes formation of stable dimers of RNase L in intact human cells as measured with a mammalian two-hybrid system. Hybrid proteins consisting of the GAL4 DNA binding domain fused to RNase L and the VP16 transactivation domain fused to RNase L were able to associate and drive transcription of a reporter gene, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…All OAS, except OASL, are interferon-induced proteins characterised by their capacity to catalyse the synthesis of 2ʹ-5ʹ-linked oligomers of adenosine from adenosine triphosphate (2-5A) [11,12] . The 2-5A binds to a latent Ribonuclease L (RNase L), which subsequently dimerises into its active form [13][14][15] . It was shown that the suppression of RNase L activity in cancer cell lines dramatically blocked cell death, which supports its role as a strong inducer of apoptosis [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…All OAS, except OASL, are interferon-induced proteins characterised by their capacity to catalyse the synthesis of 2ʹ-5ʹ-linked oligomers of adenosine from adenosine triphosphate (2-5A) [11,12] . The 2-5A binds to a latent Ribonuclease L (RNase L), which subsequently dimerises into its active form [13][14][15] . It was shown that the suppression of RNase L activity in cancer cell lines dramatically blocked cell death, which supports its role as a strong inducer of apoptosis [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…With ATP as substrate these enzymes produce 5′-phosphorylated 2′-5′ linked oligoadenylates (2-5A), which activate RNase L by binding to the ankyrin repeats and inducing dimerization, essential for the endonuclease activity of RNase L [8].…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that Tyr712 and Phe716 in this region are significantly involved in RNA binding and catalysis 9. The C‐terminal 80 residues and Lys392 are critical for dimerization,7, 10, 11 with mutants in these sites showing no dimerization or RNase activity despite normal 2‐5A binding ability.…”
Section: Introductionmentioning
confidence: 76%
“…Second, ANK is thought not to dimerize by itself, as GST‐ANK (residues 1–342) does not bind to RNase L in the presence of 2‐5A,7 and His‐ANK complexed with pApApA was shown to be a monomer by crystal structure analysis 17. Third, the dimerization sites are thought to lie in both the C‐terminal 80 residues and the protein kinase domain 10, 11. At least one of these dimerization sites should appear only after 2‐5A binding.…”
Section: Discussionmentioning
confidence: 99%